2002
DOI: 10.1037/0278-7393.28.5.908
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive categorization in unsupervised learning.

Abstract: In 3 experiments, the authors provide evidence for a distinct category-invention process in unsupervised (discovery) learning and set forth a method for observing and investigating that process. In the 1st 2 experiments, the sequencing of unlabeled training instances strongly affected participants' ability to discover patterns (categories) across those instances. In the 3rd experiment, providing diagnostic labels helped participants discover categories and improved learning even for instance sequences that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(70 citation statements)
references
References 53 publications
2
64
2
2
Order By: Relevance
“…However, the same result can easily be accommodated within the category invention framework (Clapper & Bower, 2002). Consider a hypothetical learner exposed to two different training sequences.…”
Section: Monotonicity and Models Of Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the same result can easily be accommodated within the category invention framework (Clapper & Bower, 2002). Consider a hypothetical learner exposed to two different training sequences.…”
Section: Monotonicity and Models Of Learningmentioning
confidence: 99%
“…To illustrate, consider an experiment reported by Clapper and Bower (2002;see also Clapper & Bower, 1994). In that experiment, participants saw a series of training instances (verbal descriptions of fictitious tree species) from two correlational patterns (potential categories), referred to here as A and B.…”
Section: Monotonicity and Models Of Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…M. Markman & Hutchinson, 1984;Waxman & Booth, 2001; but see also Sloutsky, 2003;Sloutsky & Fisher, 2004). A number of cognitive studies have also demonstrated the importance of category lab bels in inductive generalization (Clapper & Bower, 2002;Waldmann & Hagmayer, 2006;Yamauchi, 2005, in press; see also Murphy & Medin, 1985;Murphy & Ross, 1994;Rosch, 1978;Ross & Murphy, 1996). However, there is no clear consensus among cognitive scientists on exactly how category labels and feature labels differ.…”
mentioning
confidence: 99%